A retrospective study: Can we differentiate between repeat self-inflicted burn patients and those who commit a self-inflicted burn as an individual occurrence?. Issue 11 (November 2017) - Sayma, Meelad; Booth, Simon; Weller, Debbie; Dheansa, Baljit
Abstract: Self-inflicted burns (SIBs) are a significant cause of burns morbidity worldwide. A sub-group of SIB patients demonstrate recurrent SIB behaviour causing repeated morbidity and an increasing strain on hospital resources. The ability to predict which patients are likely to demonstrate repeat behaviour will allow for more targeted interventions in this group. This study aimed to identify the factors that differentiate patients who repeat SIB from those who commit SIB as an individual occurrence. A three-step approach was adopted: (1) initial data collection through the locally held records of the International Burns Injury Database (iBID); (2) follow-up data of SIB patient information were extracted from patient notes and (3) statistical data analysis. Seventy-five records remained for analysis. Seventeen patients were identified as going on to commit SIB more than once and so classified as 'repeat SIB' patients (22.7%). Repeat SIB patients appeared to be more commonly female and Caucasian with a mean total body surface area of less than half the individual occurrence group. The repeat SIB group was also more likely to commit burns to their limbs and demonstrate previous non-burn deliberate self-harm behaviour. 'Cold' burns were also committed more commonly in the repeat SIB group. This paper describes the largest sample of repeat SIB patients in the literature. It appears that repeat SIB patients have a set of differentiating factors that, when combined, allow for some element of prediction of these behaviours.